miR-29a-5p Regulates the Proliferation, Invasion, and Migration of Gliomas by Targeting DHRS4 - Dai, Yong; Chen, Zhenhua; Zhao, Wei; Cai, Gang; Wang, Zhifeng; Wang, Xuejiang; Hu, Hongkang; Zhang, Yi (Frontiers in Oncology, 2020)
Gliomas are the most common malignant primary brain tumors in adults and exhibit a spectrum of aberrantly aggressive phenotypes. MicroRNAs (miRNAs) play a regulatory role in various cancers, including gliomas, however, their specific roles and mechanisms have not been completely investigated. Studies have indicated that miR-29a is a tumor-suppressive miRNA, but the data are limited. In this study, we investigated the role of miR-29a-5p in glioma and explored its further mechanisms. Using a bioinformatics method，Dehydrogenase/reductase4 (DHRS4) was considered a potential target of miR-29a-5p and highly expressed in gliomas in our experiments. What’s more, using a luciferase reporter assay, DHRS4 was proved as a target gene of miR-29a-5p and correlated with glioma proliferation, invasion and migration in our vivo and vitro experiment. Simultaneously, we observed that knockdown DHRS4 rescue downregulation of gliomas proliferation, invasion, migration caused by mir-29a-5p inhibitor. The present findings demonstrated that miR-29a-5p suppresses cell proliferation, invasion and migration by targeting DHRS4, and DHRS4 may be a potential new oncogene and prognostic factor in gliomas.